Diterpenoid mới được phân lập từ cây thuốc giấu Euphorbia tithymaloides (P.) - Ính, Cầm Thị; Hồng Vân, Nguyễn Thị; Quân, Phạm Minh; Quỳnh Trang, Trần Thị; Viên, Trịnh Anh; Thuỷ, Nguyễn Thị; Thảo, Đỗ Thị (Vietnam Journal of Chemistry, 2016)
A new compound 1α,13β,14α-trihydroxy-3β-benzoyloxy-7β-methoxy-9β,15β-diacetoxyjatrophan-5,11E-dien (1), and two known compounds poly-O-acylated jatrophan diterpenoids (2, 3) were isolated and identified from Euphorbia tithymaloides (P.). Their structures were elucidated by spectroscopic methods and comparison with the reported data. Compound 1 showed good cytotoxicity against four cancer lines. Keywords. Euphorbia tithymaloides,  poly-O-acylated  jatrophan diterpenoids.